Application of generalized differential quadrature method to nonlinear bending analysis of a single SWCNT over a bundle of nanotubes - Fereidoon, A.; Babaee, A.M.; Rostamiyan, Y. (Archives of Mechanics, 2012)
The deformation of an individual single walled carbon nanotube (SWCNT) over a bundle of nanotubes has been studied using the generalized differential quadrature (GDQ) method. The effects of length, diameter, and minimum value of Lennard–Jones experimental potential have been considered in the governing equation which is derived based on the GDQ and the issues related to the implementation of the boundary and compatibility conditions were addressed. The explanation of reliability and flexibility of the GDQ is done by solving several selected examples which are evaluated by comparing them with existing exact or approximate solutions which were previously generated by finite element approach.